The Effect of Corporate Social Responsibility (CSR) on Financial Performance - Kartawinata, Budi Rustandi; Apriano, Raditya (Almana : Jurnal Manajemen dan Bisnis, 2024)
Himbara Bank has a very significant role in driving economic growth, managing national assets, and providing sustainable financial services to the community. However, its role is not only limited to financial aspects but also holds social responsibility towards society and the environment. Therefore, it is important to understand the extent to which CSR can influence Bank Himbara's financial performance in this dynamic business environment. This research aims to find information on the effect of implementing Corporate Social Responsibility (CSR) on financial performance based on Return on Equity (ROE). In this research, the population used is banks included in the Association of State-Owned Banks (Himbara) for 2019-2022. The data analysis techniques used are descriptive statistical analysis and panel data regression analysis. Based on research results, Corporate Social Responsibility (CSR) did not have a significant effect on Return on Equity (ROE) in the Association of State-Owned Banks (Himbara) in 2019-2022.